Advertising education: yesterday - today - tomorrow - Ross, Billy; Osborne, Anne; Richards, Jef (Lubbock: Graphic Services, 2006)
Este texto contiene: Advertising education : yesterday - today - tomorrow
Incluye bibliografía Includes bibliographical references and index
Keywords: Education - Advertising